Dosimetric properties of Gafchromic EBT films in medical carbon ion beams - Martišíková, Mária; Jäkel, Oliver (Physics in medicine and biology, 2010)
High spatial resolution is desired for dosimetrical verification of patient plans for radiotherapy treatments employing scanned ion beams. This is provided by Gafchromic EBT film, the ancestor of currently available EBT2 films. In this contribution, dosimetric properties of EBT films were investigated.
Gesehen am 23.05.2023